2014
DOI: 10.1016/j.jpsychires.2014.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in suicidal ideation after ketamine infusion: Relationship to reductions in depression and anxiety

Abstract: Objective Suicide is a psychiatric emergency. Currently, there are no approved pharmacologic treatments for suicidal ideation. Ketamine is an N-methyl-D-aspartate (NMDA) receptor antagonist that rapidly reduces suicidal ideation as well as depression and anxiety, but the dynamic between these symptoms is not known. The aim of this analysis was to evaluate whether ketamine has an impact on suicidal thoughts, independent of depressive and anxiety symptoms. Methods 133 patients with treatment-resistant depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 243 publications
(156 citation statements)
references
References 48 publications
6
141
1
8
Order By: Relevance
“…119 It also reduces suicidal thoughts within hours, mostly but not entirely due to reductions in depressive symptoms. 120 One RCT using an active placebo (midazolam) showed that 53% of patients treated with ketamine scored 0 on three different measures of suicidal ideation 24 hours after infusion compared with 24% of those treated with midazolam (P=0.03). 121 The reductions in conscious suicidal thoughts were also observed unconsciously through IAT testing.…”
Section: Self Poisoningmentioning
confidence: 99%
“…119 It also reduces suicidal thoughts within hours, mostly but not entirely due to reductions in depressive symptoms. 120 One RCT using an active placebo (midazolam) showed that 53% of patients treated with ketamine scored 0 on three different measures of suicidal ideation 24 hours after infusion compared with 24% of those treated with midazolam (P=0.03). 121 The reductions in conscious suicidal thoughts were also observed unconsciously through IAT testing.…”
Section: Self Poisoningmentioning
confidence: 99%
“…However, it is not clear that any other more selective NMDA receptor antagonist tested in the clinic produces comparable or improved efficacy as has been demonstrated with ketamine (Sanacora and Schatzberg, 2015). Despite the psychomimetic effects and cognitive impairment that may be produced within the first 30-45 minutes following ketamine administration, the clinical use of ketamine in depressed patients does appear to decrease suicidality (DiazGranados et al, 2010;Zarate et al, 2012;Ballard et al, 2014;Price et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the more explicit reduction of suicidal thinking, the Implicit Association Test, an assessment of suicidal cognition and potential predictor of future suicidal behavior, has been studied in the context of ketamine infusion, which has also revealed reductions in implicit suicidal thinking [Price et al 2009[Price et al , 2014. Our group recently published a secondary data analysis of 108 patients with treatment-resistant major depression (both MDD and BDep) who received a single subanesthetic dose infusion of ketamine to study the relationship between improvements in depression/anxiety and suicidality; in this sample, improvements in suicidal thinking were partially related to improvements in neuropsychiatric symptoms, explaining up to 20% of the antisuicidal effect [Ballard et al 2014]. Interestingly, in another secondary analysis of the same sample, a lack of a lifetime history of suicide attempt predicted improved antidepressant response to ketamine at 1 week post infusion [Niciu et al 2014b].…”
Section: Antisuicidal Effectsmentioning
confidence: 99%